Co-administration of vancomycin and piperacillin-tazobactam is associated with increased renal dysfunction in adult and pediatric burn patients - Hundeshagen, Gabriel (Critical care, 2017)
Burn patients are prone to infections which often necessitate broad antibiotic coverage. Vancomycin is a common antibiotic after burn injury and is administered alone (V), or in combination with imipenem-cilastin (V/IC) or piperacillin-tazobactam (V/PT). Sparse reports indicate that the combination V/PT is associated with increased renal dysfunction. The purpose of this study was to evaluate the short-term impact of the three antibiotic administration types on renal dysfunction.